Comparação de métodos in vivo e laboratoriais para avaliar o valor nutritivo de dietas para bovinos de corte - Silveira, Magali Floriano da (2006)
This experiment was carried out to compare in vivo and laboratorial methods to estimate the nutritive value of beef cattle feeds. Diets were isonitrogenous and composed by corn silage as a roughage source and 25, 40, 55 and 70 % of concentrate. Diets digestibility values measured in an in vivo digestibility assay were compared to those obtained from in situ, in vitro, in vitro/gases assays, as well from values estimated from mathematical equations. The in vivo assay was carried out using four cattle in a Latin Square design. There was not significant method by diet interaction. The in vitro method had good accuracy to estimate diets digestibility. The Weiss equation overestimated diets nutritional value due both, by overestimate fiber digestibility and by underestimate fecal endogenous excretion. As single indicators, degradation rates calculated from both, in situ e in vitro/gas assays, were not accurate to estimate the nutritive value of feeds.